Impact of Habitat Variability on Phenotypic Traits and Seed Germination Performance of Euphorbia helioscopia L.; a Case Study from the Kashmir Himalaya, India: Impact of Habitat Variability on Phenotypic Traits of Euphorbia helioscopia L. - Islam, Tajamul; Zargar, Shabir A.; Magray, Junaid A.; Nawchoo, Irshad A. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Euphorbia helioscopia L. (Euphorbiaceae), is an important medicinal plant species of the Himalayan region. The species showed wide variability in its phenotypic traits under different environmental conditions. The purpose of this study was to determine the impact of elevational gradient on the morphological traits and reproductive features of the species. The plants grown in the Kashmir University Botanical Garden were more vigorous and taller than the plants of high-altitude sites. Principal component analysis (PCA) revealed that the habitat of KUBG and Kangan (Ganderbal) were comparatively facilitated the growth of E. helioscopia. The regression analysis showed a positive correlation between various morphological traits. Our attempted results highlighted an elaborated account of the variation of phenotypic traits and seed germination performance in response to different environmental conditions along an elevational gradient.